Evaluation of maize (Zea mays)-legumes intercropping system under red and lateritic tract of West Bengal (SAARC Journal of Agriculture, 2014)
A field experiment was carried out during kharif season of 2010 and 2011 at Sriniketan Research Farm, Visva-Bharati, West Bengal, India. The yield attributes and growth parameters were significantly higher in case of sole maize and intercropping treatments with legumes. The maximum total chlorophyll (chlorophyll a + chlorophyll b) was observed on sole maize, which was statistically at par with maize crop under intercropping system. In the middle canopy, highest light interception (%) was observed in maize + groundnut (2:4). The grain yield (2.48 t ha-1) and stover yield (5.07 t ha-1) of maize were significantly higher in sole maize than either of its intercropping systems with legumes. The legume yield was highest in maize + groundnut (1:2) followed by sole groundnut. The maize equivalent yield (7.06 t ha-1) was highest in maize + groundnut (2:4) followed by maize + groundnut (1:2). The highest benefit cost ratio maize + groundnut (1:2) closely followed by maize + soybean (1:2). The total N uptake by sole maize was significantly higher and under intercropping systems, the highest N concentrations in grain and straw, and protein content in grains were obtained in maize + soybean (1:2) and maize + groundnut (2:4) treatment. DOI: http://dx.doi.org/10.3329/sja.v12i1.21118 SAARC J. Agri., 12(1): 117-126 (2014)